Laparoscopic anatomical partial splenectomy for extremely rare isolated splenic lymphangioma in an adult: a case report and literature review - Shi, Ruizi; Yang, Pei; Guo, Yangjie; Tang, Yiping; Luo, Hua; Qin, Chuan; Jiang, Ting; Huang, Yu; Gao, Ziqing (Frontiers in Oncology, 2024)
BackgroundBenign tumors of the spleen are rare compared to those of other parenchymal organs, accounting for less than 0.007% of all tumors, and are often found incidentally. Splenolymphangiomas are much rarer, commonly occur in children, and tend to have multiple foci. Splenic lymphangiomas are rare in adults, and fewer than 20 adult patients with isolated splenic lymphangiomas have been reported. In this article, we report the case of a middle-aged female patient with isolated splenic lymphangioma who underwent laparoscopic anatomical hypophysectomy of the lower pole of the spleen. We also summarize the existing literature on splenic lymphangioma diagnosis and available treatment options.Case presentationA 58-year-old middle-aged woman was found to have a mass approximately 60 mm in diameter at the lower pole of the spleen during a health checkup that was not accompanied by other symptoms or examination abnormalities. After completing a preoperative examination with no contraindications to surgery, the patient underwent laparoscopic anatomical splenectomy of the lower extremity of the spleen. The patient recovered well without complications and was discharged from the hospital on the 7th postoperative day. Histopathological and immunohistochemical results confirmed the diagnosis of splenic lymphangioma. Prompt surgical intervention is safe and necessary when splenic lymphangiomas are large or associated with a risk of bleeding.ConclusionSplenic lymphangiomas are rare and require early surgical intervention in patients with large tumor diameters or those at risk of rupture and bleeding. After rigorous preoperative evaluation and preparation, laparoscopic anatomical partial splenectomy is safe and feasible for surgeons with experience in laparoscopic surgery.